2021
DOI: 10.22541/au.160968257.71855237/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absence of association between 2019–20 influenza vaccination and COVID-19: results of the European I-MOVE-COVID-19 primary care project, March–August 2020

Abstract: Background Claims of influenza vaccination increasing COVID-19 risk are circulating. Within the I-MOVE-COVID-19 primary care multicentre study, we measured the association between 2019–20 influenza vaccination and COVID-19. Methods We conducted a multicentre test-negative case-control study at primary care level, in study sites in five European countries, from March–August 2020. Patients presenting with acute respiratory infection were swabbed, with demographic, 2019–20 influenza vaccination and clinical infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Of the 92 full-text articles identified, 58 were excluded because they did not meet the inclusion criteria, and two others were obtained from the references. The remaining 36 articles reported on 55,996,841 subjects outcomes were included in this analysis [21–56] . None of the participants had received COVID-19 vaccination during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 92 full-text articles identified, 58 were excluded because they did not meet the inclusion criteria, and two others were obtained from the references. The remaining 36 articles reported on 55,996,841 subjects outcomes were included in this analysis [21–56] . None of the participants had received COVID-19 vaccination during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza and COVID-19 are different respiratory viral diseases that can be clinically indistinguishable and co-exist at the same period. Some preliminary studies suggest some protection against SARS-CoV-2 to be conferred from vaccination to other pathogens such as influenza [14] while others have produced contrasting result [39]. There is also a limited number of studies that examined the association of the pneumococcal vaccine with the risk of developing SARS-CoV-2 infection and disease severity or risk of death on COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The booster Bacillus Calmette-Guérin (BCG) vaccine was suggested, by many studies and even by a meta-analysis, to have beneficial effects on preventing COVID-19 infection [11][12][13]. Some preliminary studies suggest some protection against SARS-CoV-2 to be conferred from vaccination to other pathogens such as influenza [14] while others have produced contrasting results [15]. In this regard, we conducted a systematic review and meta-analysis to assess the overall association between influenza and pneumococcal vaccination and SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction in risk of COVID-19 infection and severe disease has been reported following receipt of influenza vaccine in several studies [16][17][18], although this association was not observed in other studies. [19][20][21][22][23] A prior study at KPSC found a reduction in risk of COVID-19 diagnosis and severe disease associated with receipt of 13-valent pneumococcal conjugate vaccine (PCV13) but not with receipt of influenza vaccine. [24] Interestingly, in a sensitivity analysis among the subset of individuals who received influenza vaccine but no other vaccines, we found that receipt of RZV was still associated with a similar reduction in risk of COVID-19 diagnosis and hospitalization, suggesting that influenza vaccination or healthy vaccinee bias had minimal impact on our findings.…”
Section: Discussionmentioning
confidence: 99%